2014
DOI: 10.1186/1745-6215-15-352
|View full text |Cite
|
Sign up to set email alerts
|

Use of ivabradine and atorvastatin in emergent orthopedic lower limb surgery and computed tomography coronary plaque imaging and novel biomarkers of cardiovascular stress and lipid metabolism for the study and prevention of perioperative myocardial infarction: study protocol for a randomized controlled trial

Abstract: BackgroundThe incidence of perioperative myocardial infarction (PMI) globally is known to be around 2 to 3% and can prolong hospitalization, increased morbidity and mortality. Little is known about the pathophysiology and risk factors for PMI. We investigate the presence of elevated novel cardiac markers and preoperative coronary artery plaque through contemporary laboratory techniques to determine the correlation with PMI, as well as studying ivabradine and atorvastatin as protective pharmacotherapies against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 89 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…Patients will be assessed with ECG, cardiac echo, cardiac biomarkers and CT coronary angiography. The primary outcome will be post-operative TnI measurements to define myocardial injury [ 28 ], however this has not been reported seven years post publication of methodology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients will be assessed with ECG, cardiac echo, cardiac biomarkers and CT coronary angiography. The primary outcome will be post-operative TnI measurements to define myocardial injury [ 28 ], however this has not been reported seven years post publication of methodology.…”
Section: Discussionmentioning
confidence: 99%
“…The focus of the failed POST-OP RCT [ 27 ] and unreported RCT of Rudd et al [ 28 ] is the anti-inflammatory effects of statins, proposed to help increase long-term survival [ 5 ]. Hip fracture is associated with a heightened inflammatory response which represents an independent predictor for mortality and morbidity [ 30 ], however, the long-term anti-inflammatory effects of the statins in an immune-primed and cardiovascularly-vulnerable hip fracture cohort was not able to be examined by this study.…”
Section: Discussionmentioning
confidence: 99%
“…Mobile Information Systems scientific reference for the prevention of CHD and the development of relevant therapies [21], as well as to give a reference for preconception and prenatal health care. [10,11,22].…”
Section: Related Workmentioning
confidence: 99%
“…Zhao et al performed neonatal screening for CHD and showed that the prevalence of CHD in children in Shanghai was 26.6‰ and showed that the prevalence of CHD in infants aged 0-1 year was 8.15‰ in Guangdong Province [7,8]. The incidence of perinatal CHD in Gansu Province increased year by year from 12.66 per million in 2005 to 17.38 per million in 2010 [9,10], and the ranking increased from third in 2005 to first in 2010. Currently, most of the findings suggest that CHD is caused by a combination of genetic and environmental factors [11].…”
Section: Introductionmentioning
confidence: 99%